Epigenetics in Prostate Cancer. (30th November 2011) - Albany, Costantine; Alva, Ajjai S.; Aparicio, Ana M.; Singal, Rakesh; Yellapragada, Sarvari; Sonpavde, Guru; Hahn, Noah M.
Abstract : Prostate cancer (PC) is the most commonly diagnosed nonskin malignancy and the second most common cause of cancer death among men in the United States. Epigenetics is the study of heritable changes in gene expression caused by mechanisms other than changes in the underlying DNA sequences. Two common epigenetic mechanisms, DNA methylation and histone modification, have demonstrated critical roles in prostate cancer growth and metastasis. DNA hypermethylation of cytosine-guanine (CpG) rich sequence islands within gene promoter regions is widespread during neoplastic transformation of prostate cells, suggesting that treatment-induced restoration of a "normal" epigenome could be clinically beneficial. Histone modification leads to altered tumor gene function by changing chromosome structure and the level of gene transcription. The reversibility of epigenetic aberrations and restoration of tumor suppression gene function have made them attractive targets for prostate cancer treatment with modulators that demethylate DNA and inhibit histone deacetylases.